SWEARING ANALYSIS OF CHARACTERS IN DEADPOOL MOVIE - Wulandari, Tasya; Firmawan, Hendro (Universitas Gunadarma, 2019)
This research focuses to identify the types and the reasons of swearing for characters of Deadpool movie. It uses a qualitative method to analyzing the data that are found. It finds 81 data of types of swearing, and 83 data of reasons of swearing out of 83 data. The data of this research are in the form of sentences, words spoken by the characters. This research finds that the types of swearing uttered by the characters of Deadpool movie can be classified into five types, there are, Dyphemistic Swearing (DS), Abusive Swearing (AS), Idiomatic Swearing (IS), Emphatic Swearing (ES), and Cathartic Swearing (CS). In addition, it also found the the reason of swearing that is consist of three motives. There are, Psychological motives (PM), Social Motives (SM), and Linguistic Motives (LM). From this research, it can be concluded that emphatic swearing is the most used swearing expression and psychological motives is the most dominant reasons spoken by the characters.